Surface Effects in State-Resolved Gas-Surface Reactions - High, Eric. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Chemistry.; Advisor: Arthur Utz.; Committee: E. Charles Sykes, Yu-Shan Lin, and Sylvia Ceyer.; Keywords: Chemistry, and Physical chemistry.